A Review on Wireless Sensor Network Using LEACH Protocol for Improving Lifespan of Sensor Nodes - Gupta, Akash; Srivastava, Rishi Kumar (International Journal of Computer Sciences and Engineering, 2025)
With the limitation of the power utilization in wireless device nodes. The creation is intended to recover the hindrance of capacity breakdown and lifetime of the sensor node. Each sensor node is associated with a memory and has less power requirement. The main aspiration of this paper is to make the node active and consume less energy for transmitting or receiving the data from the sensor node. The paper considers three approaches such as LEACH and PEGASIS algorithm.